2023
DOI: 10.3390/su15064916
|View full text |Cite
|
Sign up to set email alerts
|

Differences in COVID-19 Policies and Income Distribution: A Cross-Country Comparison

Abstract: This paper looks at the distribution of disposable income by deciles to indicate how specific mitigating measures have influenced income groups and considers the effectiveness of different combinations of containment measures in the European Union. Simulations using the EUROMOD tax-benefit microsimulation model imply that the mitigating effects of the simulated measures are regressive, with a bigger influence on the bottom part of the income distribution. It is also observed that old democracies benefit from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
“…At the level of household income, cross-country evidence suggests that the poorest among the households benefited most from compensatory policy measures, while the disposable income of the best-placed households suffered less from containment measures [4][5][6]. Evidence from Malaysia indicated that households with low incomes were unaffected by pandemic restrictions or even benefited [7].…”
Section: Literature Reviewmentioning
confidence: 99%